PENGARUH E-SERVICE QUALITY TERHADAP E-LOYALTY MELALUI E-TRUST PADA PELANGGAN FERINESIA MOBILE DI PT.UKI RAYA LINES CAB.KENDARI - Dzulfikri Azis Muthalib; Haprisia; Nasrul; Feliks Anggia Binsar Kristian Panjaitan (Jurnal Multidisipliner Bharasumba, 2026)
The objectives of this study are: (1) To determine and analyze the influence of e-service quality on e-loyalty of Ferinesia Mobile Customers at PT. Uki Raya Lines Cab.Kendari. To determine and analyze the influence of e-service quality on e-trust of Ferinesia Mobile Customers at PT. Uki Raya Lines Cab.Kendari. To determine and analyze the influence of e-trust on e-loyalty of Ferinesia Mobile Customers at PT. Uki Raya Lines Cab.Kendari. To determine and analyze the influence of e-service quality on e-loyalty through e-trust of Ferinesia Mobile Customers at PT. Uki Raya Lines Cab.Kendari. The population in this study were all Ferinesia Mobile customers at PT. Uki Raya Lines Cab.Kendari. The sample in this study was 100 respondents using the lemeshow formula. The data analysis technique used Partial Least Square (PLS) with a calculation process assisted by the Smart PLS 4 program. The results of the study showed that: e-service quality had a positive and significant effect on e-loyalty. E-service quality has a positive and significant effect on e-trust. E-trust has a positive and significant effect on e-loyalty. E-service quality has a positive and significant effect on loyalty through e-trust.